Modelling of glass‐like carbon structure and its experimental verification by neutron and X‐ray diffraction. Issue 1 (12th December 2016) - Jurkiewicz, K.; Duber, S.; Fischer, H. E.; Burian, A.
Abstract : This paper reports the characterization of the atomic structure of a series of glass‐like carbons by wide‐angle neutron and X‐ray scattering and molecular dynamics simulations. Abstract : Glass‐like carbon is a well known carbon form that still poses many challenges for structural characterization owing to a very complex internal atomic organization. Recent research suggests that glassy carbon has a fullerene‐related structure that evolves with the synthesis temperature. This article reports on direct evidence of curved planes in glassy carbons using neutron and X‐ray diffraction measurements and their analysis in real space using the atomic pair distribution function formalism. Changes in the structure including the degree of curvature of the non‐graphitizing glassy carbons as a function of the pyrolysis temperature in the range 800–2500°C (1073–2773 K) are studied using optimized models of the atomic structure. Averaged models of single coherent scattering domains as well as larger structural fragments consisting of thousands of atoms were relaxed using classical molecular dynamics. For such models the diffraction intensities and the pair distribution functions were computed. The compatibility of the computer‐generated models was verified by comparison of the simulations with the experimental diffraction data in both reciprocal and real spaces. On the basis of features of the developed structural models for glass‐like carbons, the origin of the properties such as high strength and hardness and low gas permeability can be better understood.